The Soundmark of Tradition: Communicative Functions of Pentatonic Music in the Gula Gending Street Trade of West Nusa Tenggara - Galih Suryadmaja; Nurtikawati Nurtikawati; Salniwati Salniwati; Qian Xiang Yun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2026)
This study investigates the communicative functions of pentatonic music in the Gula Gending street vending practice in West Nusa Tenggara, Indonesia, positioning it as a culturally embedded soundmark within everyday economic activity. While previous soundscape scholarship has largely foregrounded environmental listening, relatively little attention has been paid to the ways in which structured musical systems function as active communicative agents in informal economic contexts. Adopting an ethnomusicological ethnographic approach, this research integrates participant observation, in-depth interviews, and audio-visual documentation to examine the intersections between musical structure, performance practice, and socio-cultural context. The findings demonstrate that Gula Gending music operates as a multi-layered communicative system: it serves as an auditory marker of identity, a mechanism for attracting attention, a medium for transmitting cultural memory, and a facilitator of social interaction between vendors and consumers. The deployment of pentatonic structures enhances perceptual accessibility, enabling rapid recognition and response within fluid and dynamic street environments. Beyond its functional dimension, the music embodies symbolic meanings that link individual experience to broader collective cultural identities. This study contributes to ethnomusicology and sound studies by reconceptualizing the notion of soundmark as an active semiotic and economic practice rather than a passive acoustic phenomenon. Furthermore, it highlights the capacity of traditional musical forms to operate as adaptive communicative strategies within contemporary informal economies, offering critical implications for cultural sustainability and policy formulation.